Slow cord dorsum potentials elicited by descending volleys in man. Issue 3 (March 1979) - Shimizu, H; Shimoji, K; Maruyama, Y; Sato, Y; Harayama, H; Tsubaki, T
Abstract : Human cord dorsum potential (CDP) was recorded from the posterior epidural space at the levels of cervical and lumbar enlargements, using epidural catheters as the recording electrodes, in 15 normal volunteers and six patients suffering from amyotrophic lateral sclerosis. In normal subjects the CDP elicited by descending volleys consisted of spike potentials followed by sharp negative and slow positive waves which were very similar to the P1, N1, and P2 potentials, respectively, of the CDP evoked segmentally. By contrast, in all patients with amyotrophic lateral sclerosis both the sharp negative and slow positive waves were absent in the CDP elicited by descending volleys, while the pattern of each component of the segmentally evoked CDP remained unchanged. Thus, the sharp negative and slow positive waves of human CDP elicited by descending volleys might reflect the activity of interneurones and primary afferent depolarisation respectively, produced by impulses through the corticospinal tract.